THE IMPACT OF EFFECTIVENESS OF ELECTRONIC DOSSIER-BASED PERSONNEL INFORMATION SYSTEMS AND IT INFRASTRUCTURE READINESS IN ENHANCING THE QUALITY OF PERSONNEL SERVICES IN THE INDONESIAN ARMY : Pengaruh Efektivitas Sistem Informasi Aplikasi Personel Berbasis Dosir Elektronik dan Kesiapan Infrastruktur Teknologi Informasi dalam Meningkatkan Kualitas Pelayanan Personel TNI AD - Lukman Yudho Prakoso; Resmanto Widodo Putro; Dikki Kurniawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Digital transformation in personnel administration management is an urgent need for military institutions such as the Indonesian Army (TNI AD). This study aims to evaluate the effectiveness of the Electronic Personnel File Information System Application (SIAP Dosel) in improving the quality of personnel management in Ditajenad and analyze the readiness of Information Technology (IT) infrastructure and human resources (HR) supporting its implementation. The research method used is quantitative, with a survey approach involving 63 respondents from various Army units. The data were analyzed using regression analysis techniques to examine the relationship between the effectiveness of SIAP Dosel, IT infrastructure readiness, and HR readiness on the quality of personnel administration services. The results indicate that the effectiveness of SIAP Dosel, IT infrastructure readiness, and HR readiness positively and significantly affect the improvement of personnel administration service quality. The study concludes that optimizing SIAP Dosel, supported by adequate IT infrastructure and trained HR, can accelerate administrative processes, enhance data accuracy, and facilitate better decision-making within the Indonesian Army.